Recent insights on the impact of SWELL1 on metabolic syndromes - Qin, Mianhong; Yi, Xuejie; Duan, Ziqiang; Chang, Bo; Li, Tao (Frontiers in Pharmacology, 2025)
SWELL1 is a key component of the volume-regulated anion channel (VRAC) and participates in cell volume regulation as an ion channel plasma membrane protein. While early studies focused on its role in immune cell development and tumor progression, recent studies have revealed that SWELL1 plays an important role in metabolic diseases. Studies have shown that SWELL1 is extensively involved in physiological processes in peripheral metabolic tissues, including adipocyte hypertrophy, skeletal muscle volume regulation, insulin secretion, and hepatic lipid metabolism through interactions with the insulin signaling pathway. These functions play key roles in the pathogenesis of obesity, type 2 diabetes mellitus (T2DM), and non-alcoholic fatty liver disease (NAFLD), suggesting that SWELL1 may be a new target for the treatment of metabolic diseases. In this review, we focus on the structural and functional characteristics of SWELL1 to provide an in-depth explanation of its role in the development of metabolic syndrome, especially the regulation of the insulin signaling pathway, and provide a basis for the development of therapeutic strategies for metabolic diseases targeting SWELL1.